Resistance genomics and molecular epidemiology of high-risk clones of ESBL-producing Pseudomonas aeruginosa in young children - Patil, Sandip; Chen, Xiaowen; Dong, Shaowei; Mai, Huirong; Lopes, Bruno Silvester; Liu, Sixi; Wen, Feiqiu (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The emergence of multidrug-resistant Pseudomonas aeruginosa poses a global threat, but the distribution and resistance profiling are unclear, especially in young children. Infections due to P. aeruginosa are common, associated with high mortality, and increasingly β-lactam drug resistant. Methods We studied the molecular epidemiology and antibiotic resistance mechanisms in 294 clinicalisolates of P. aeruginosa from a pediatric hospital in China. Non-duplicate isolates were recovered from clinical cases and were identified using an API-20 kit followed by antimicrobial susceptibility testing using the VITEK®2 compact system (BioMerieux, France) and also by broth dilution method. In addition, a double-disc synergy test for the ESBL/E-test for MBL was performed. The presence of beta-lactamases, plasmid types, and sequence types was determined by PCR and sequencing. Results Fifty-six percent (n = 164) of the isolates were resistant to piperacillin–tazobactam, followed by cefepime (40%; n = 117), ceftazidime (39%; n = 115), imipenem (36%; n = 106), meropenem (33%; n = 97), and ciprofloxacin (32%; n = 94). Forty-two percent (n = 126) of the isolates were positive for ESBL according to the double-disc synergy test. The blaCTX-M-15 cephalosporinase was observed in 32% (n = 40/126), while 26% (n = 33/126) werepositive for blaNDM-1 carbapenemase. Aminoglycoside resistance gene aac(3)IIIawas observed in 16% (n = 20/126), and glycylcyclines resistance gene tet(A) was observed in 12% (n = 15/126) of the isolates. A total of 23 sequence types were detected, including ST1963 (12%; n = 16), followed by ST381 (11%; n = 14), ST234 (10%; n = 13), ST145 (58%; n = 10), ST304 (57%; n = 9), ST663 (5%; n = 7), and a novel strain. In ESBL-producing P. aeruginosa, 12 different Incompatibility groups (Inc) were observed, the most common being IncFI, IncFIS, and IncA/C. The MOBP was the most common plasmid type, followed by MOBH, MOBF, and MOBQ. Discussion Our data suggest that the spread of antibiotic resistance is likely due toclonal spread and dissemination of different clinical strains of P. aeruginosa harbouring different plasmids. This is a growing threat in hospitals particularly in young children which needs robust prevention strategies.